Peran Bumdes Mangrove Maju Bersama Tanjung Rejo dalam Meningkatkan Kesejahteraan Masyarakat di Desa Tanjung Rejo Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Natal Fernando Panjaitan; Agus Suriadi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
Village development is the main foundation of the national development plan to address the issue of high rural poverty. This study aims to analyze the role of the Mangrove Maju Bersama Village-Owned Enterprise (BUMDes) in Tanjung Rejo Village, Deli Serdang, in efforts to improve community welfare through the ecotourism sector and mangrove management. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation. Informants consisted of BUMDes administrators, village officials, and beneficiary communities. The results showed that BUMDes played a crucial role in job creation, income generation (through business diversification such as shrimp farming and handicrafts), and strengthening social participation and environmental conservation. Positive impacts were significantly observed in indicators of community health, education, and housing quality. Despite facing challenges such as limited capital and managerial capacity, BUMDes succeeded in making a substantial contribution to Village Original Income (PAD) and local economic empowerment. Despite the challenges faced by BUMDes, including limited financial resources and the need for enhanced managerial skills, its achievements in contributing to the village's economic empowerment and environmental sustainability are commendable. With continued support and capacity building, BUMDes can further expand its role in addressing rural poverty and enhancing the overall development of Tanjung Rejo Village.